La filosofía institucional y la planificación en el desarrollo institucional, de la comunidad educativa, de la escuela fiscal mixta “Buenos Aires”, del barrio San Francisco, de la parroquia Lauro Guerrero, del cantón Paltas, de la provincia de Loja, en el período 2012 – 2013 - Tacuri Guaman, Hernan Amable (2013)
The philosophy and the planning in the institution building, are today's news and educational importance and of investigation, the results obtained of the application of the survey to executives, teachers, students and family parents, use as much to improve the institutional prestige. The scanty participation of teachers, students and family parents in the production of the mission, socialization and evaluation of the achievement of the institutional aims, institutional diagnosis, obtaining of the aims raised in the institutional planning, diagnosis and socialization of the Educational Institutional Project, they are results that worry and deserve an immediate attention. Small demonstration of the fulfillment of the commitments, limited practice of the values defined by the community, restricted institutional organization, scanty participation in the selection of strategies and in the management of the activities of the Operative Annual Plan; and, the inexperience of the teachers in the managing of the TICS, they are problems that concern the institution and that deserve immediate solution. The climate organizacional that lives through the Educational Institution, always has stimulated the work and has generated leaders, the limited evaluation of the Institution building and the deficient increase of the school performance intervene in the institutional prestige. Key words: philosophy, planning, development and institutional prestige.